Getting smarter with data: understanding tensions in the use of data in assurance and improvement-oriented performance management systems to improve their implementation - Karen Gardner; Sue Olney; Helen Dickinson (BMC, 2018)
Abstract Background A better understanding of the conditions under which performance indicators can be used to improve accountability for outcomes and promote quality improvement could help policy-makers develop more effective performance management systems. One problem is the lack of conceptual models and empirical data that describe the processes through which different approaches use data together with other incentives to influence motivation. Discussion Drawing on the performance governance and quality improvement literature, we developed a framework that distinguishes between the practice of using information to verify levels of performance in market-oriented performance management approaches and using indicators to monitor and promote improvement through building capacity for using data in service and professional networks. The framework explores how performance indicators are deployed and used in the different approaches to enact accountability or stimulate motivation for improvement and articulates the types of system architecture and processes needed to advance implementation. Summary The framework encourages a critical appraisal of the motivations, reward systems and techniques that underpin different performance management approaches. Understanding how and for what purpose performance information is used in everyday practice will advance theory and help inform decision-makers in designing the conditions that effectively contribute to performance accountability and improvements.